Effect of experimental solution and varnish containing titanium tetrafluoride (TiF4) on prevention of tooth erosion - Vertuan, Mariele (2025)
This study aimed to: 1- develop erosive tooth wear (ETW) in an animal model and evaluate the efficacy and safety of titanium tetrafluoride (TiF4) in preventing ETW; 2- investigate the protective role of a titanium tetrafluoride/sodium fluoride (TiF4/NaF) solution in a randomized, double-blind, parallel, placebo-controlled in vivo study model, as well as the participants\' perception regarding the use of this experimental solution. Forty-eight male Wistar rats were divided into three groups (n=16): TiF4 (2.45% F), NaF (2.45% F) and placebo varnishes. Eight from each group were subjected to erosive challenges (Sprite® Zero) and the other received tap water, both ad libitum. After twenty-eight days, the mandibles were resected for histopathological gingival analysis, clinical and microscopic tooth evaluation by 3D confocal laser microscopy (CLM), scanning electron microscopy (SEM-EDX) and micro-Raman spectroscopy (MRS). Organs were evaluated with respect to fluoride content. The data were submitted to statistical analysis (p<0.05). After the ethics approval, 33 selected participants were divided into three treatments: TiF4/NaF solution (500 ppm F, pH 4.4); AmF/NaF/SnCl2- mouthwash (500 ppm F, pH 4.5) and water (pH 7.0) (n=11). After professional cleaning, the participants rinsed with one of the solutions for one minute and waited two hours for the erosive challenge. The erosive solution (1% citric acid, pH 2.5) was applied for 10 s on each central incisor (area: 4mm2) and collected for calcium analysis using III Arsenazo colorimetric method. The Ca2+ release data were compared using Kruskal-Wallis/ Dunn tests (p<0.05). In relation to the animal model, no significant difference was found in F content in tissues. No histopathological damage was seen in gingiva. ETW was clinically more aggressive in rats from placebo group consuming Sprite® compared to water (Q²=12.6, p<0.01), in accordance with confocal images. TiF4 was superior in reducing tooth area loss (0.036±0.01m2) compared to NaF and placebo (0.044±0.01/0.063±0.01m2 , ANOVA, p<0.0001). Dentin exposure was detected by SEM in rats belonging to placebo consuming Sprite®. Peaks compatible with typical apatite bands were visible. On the other hand, in the clinical in vivo model, teeth treated with both fluoride solutions released less calcium into the acid (median and interquartile range: TiF4/NaF 0.45/0.19 mM and AmF/NaF/SnCl2 0.46/0.15 mM Ca2+, p=0.99) compared to the negative control (1.12/0.42 mM Ca2+, 60% reduction, p<0.0006). For both F solutions, only one participant per group reported unpleasant taste. Four participants belonging to AmF/NaF/SnCl2-mouthwash reported burning sensation post-rinse, while only one participant described such feeling after TiF4/NaF rinsing. The TiF4 varnish reduces the progression of ETW without causing any relevant side-effect and the rats model was able to simulate ETW in vivo. The experimental TiF4/NaF solution was as effective as the commercial AmF/NaF/SnCl2- mouthwash in protecting enamel against erosive demineralization with a good acceptability by the participants.